(untitled) (Phenomenology, Humanities and Sciences, 2023)
This article starts from the questioning about the relationship between spirituality and psychotherapy, according to the perceptions of Gestalt therapists. It aims to describe how such psychotherapists perceive the theme of spirituality and its presence in the clinic, as well as how it is handled in the psychotherapeutic context. The material presented here brings part of the results obtained in a more comprehensive empirical research, in which the qualitative and phenomenological method was used for data collection and analysis, as conceived by Amedeu Giorgi. Semi-structured interviews were conducted with five Gestalt therapists with extensive clinical experience. The study resulted in the apprehension of essential components of the participants’ experiences, which included the presence of existential and transcendent themes in the clinic, the importance of the therapeutic relationship and the phenomenological posture, the integration between the spiritual and psychic dimensions, their possible relationships with religion, as well as the psychotherapist’s own spirituality.